Effects of voluntary running on the skeletal muscle of rats with pulmonary artery hypertension - Drummond, Filipe Rios; Soares, Leôncio Lopes; Leal, Tiago Ferreira; Leite, Luciano Bernardes; Rezende, Leonardo Mateus Teixeira; Fidelis, Meilene Ribeiro; Lavorato, Victor Neiva; Miranda, Denise Coutinho; Carneiro-Júnior, Miguel Araújo; Neves, Mariana Machado; Alberici, Luciane Carla; Carlo Reis, Emily Correna; et al. (Frontiers in Physiology, 2023)
We tested the effects of voluntary running on the skeletal muscle of rats with pulmonary artery hypertension (PAH). PAH was induced in rats by a single injection of monocrotaline (MCT, 60 mg/kg). Rats in the sedentary hypertension (SH) group had their tolerance to physical effort reduced throughout the experiment, while those in the sedentary control (SC), exercise control (EC), exercise hypertension (EH) and exercise median (EM) groups did not. Despite that, the muscular citrate synthase activity was not different between groups. The survival time was higher in the EH group (32 days) than in the SH group (28 days). SH and EH groups showed a lower percentage of muscle fiber and a higher percentage of extracellular matrix compared to control groups. However, the EM and EH groups presented higher percentage of muscle fiber and lower percentage of extracellular matrix than SH group. Regarding muscular gene expression, the SH and EM groups showed a lower expression of PGC1-α and a higher expression of VEGF compared to SC group, while PGC1-α was elevated in the EH group. No difference between groups was found for the carbonylated protein levels, while the TNF-α/IL-10 ratio was augmented in the EH group. In conclusion, voluntary running augments the proportion of fiber and affects the gene expression of inflammatory and mitochondrial biogenesis’ markers in the skeletal muscle of rats with MCT-induced PAH, which benefits their survival and tolerance to physical effort.